Batı'ya Yön Veren Metinler II (2010)
The defeats and losses of lands since the last quarter of the 16th century prompted intellectuals in Muslim countries, particularly the Ottoman Empire, to look for ways of overcoming their weakness against the West. The foremost notion in the various theses developed in this context is that the problem stems from the basic values of Islam and the practices of the Prophet and his Companions. According to this view, the main reason for the defeat of the Islamic world by the Western states can be attributed to the lack of development of a cultural infrastructure that can produce the type of businessman who can take the necessary risks for the development of capitalism.